2012
DOI: 10.1534/g3.112.003459
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation, Stability, and Isolate-Specificity of QTL for Resistance toPhytophthora infestansin Cultivated Tomato (Solanum lycopersicum)

Abstract: Cultivated tomato (Solanum lycopersicum) is susceptible to late blight, a major disease caused by Phytophthora infestans, but quantitative resistance exists in the wild tomato species S. habrochaites. Previously, we mapped several quantitative trait loci (QTL) from S. habrochaites and then introgressed each individually into S. lycopersicum. Near-isogenic lines (NILs) were developed, each containing a single introgressed QTL on chromosome 5 or 11. NILs were used to create two recombinant sub-NIL populations, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 87 publications
3
67
0
Order By: Relevance
“…Genomic DNA extractions, genotyping with chromosome 5 PCR-based markers (SCAR, CAPS, and SSR), primer sequences, enzymatic reaction conditions, and restriction enzymes used for each marker have been described by Johnson et al (2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA extractions, genotyping with chromosome 5 PCR-based markers (SCAR, CAPS, and SSR), primer sequences, enzymatic reaction conditions, and restriction enzymes used for each marker have been described by Johnson et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…In a companion study (Johnson et al 2012), we mapped the chromosome 5 resistance QTL reported by Brouwer and St. Clair (2004) at higher resolution with sub-NILs. We found that the resistance QTL located in a 12.3 cM region subsequently fractionated into two and three QTL groups for foliar and stem resistance, respectively.…”
mentioning
confidence: 99%
“…There is significant physiological crosstalk between shade avoidance, drought physiology, and phenology (Maliakal Schmitt et al, 2003), raising the possibility that CSA1 pleiotropically affects phenological and physiological traits in the TSUxKAS population, a hypothesis that requires further testing. Several studies have found that single QTL peaks can fractionate into multiple linked peaks, each caused by separate, but linked polymorphisms (Studer and Doebley, 2011;Johnson et al, 2012). To examine this possibility, we screened for QTLs with multiple strong candidate genes with correlated expression patterns.…”
Section: Candidate Genes For Drought Adaptationmentioning
confidence: 99%
“…Pleiotropy remains uncommon in maize, and correlated responses may be due to While in some cases single genes or alleles common across diverse germplasm confer disease resistance, increasingly, the role of structural variation in plants is being explored and its effects on phenotypic variation recognized (Springer et al 2009;Chia et al 2012;McHale et al 2012). As quantitative trait loci (QTL) are subjected to fine mapping, some loci fractionate into many QTL, each conditioned by one or more genes (Steinmetz et al 2002;Studer and Doebley 2011;Johnson et al 2012). In some cases, the allele effect conditioned by each QTL is small enough that the individual locus cannot be identified in isolation (Buckler et al 2009;Poland et al 2011).…”
mentioning
confidence: 99%
“…As quantitative trait loci (QTL) are subjected to fine mapping, some loci fractionate into many QTL, each conditioned by one or more genes (Steinmetz et al 2002;Studer and Doebley 2011;Johnson et al 2012). In some cases, the allele effect conditioned by each QTL is small enough that the individual locus cannot be identified in isolation (Buckler et al 2009;Poland et al 2011).…”
mentioning
confidence: 99%